Accuracy of CT angiography for detecting ruptured intracranial aneurysms - Mkhize, Nomasonto N.; Mngomezulu, Victor; Thandi E. Buthelezi (AOSIS Publishing, 2023)
Background: Digital subtraction angiography (DSA) is invasive, costly and unavailable in many South African hospitals; however, it remains the gold standard for imaging intracranial aneurysms. CT angiography (CTA) is a non-invasive and readily available screening tool prior to DSA. Objectives: This study aimed to evaluate the diagnostic performance of CTA in detecting ruptured intracranial aneurysms using DSA as the reference standard and to determine the effect of aneurysm size and location on CTA sensitivity. Method: A retrospective analysis of CTA and DSA data from reports of patients suspected to have aneurysmal subarachnoid haemorrhage (SAH) at Chris Hani Baragwanath Academic Hospital between January 2017 and June 2020. Results: Conventional DSA detected aneurysms in 94 out of 115 patients; while of these, CTA detected 75 and missed 19. The CTA sensitivity, specificity and accuracy was 80%, 43% and 73%, respectively. The CTA sensitivity for aneurysms < 3 mm and 3 mm – 5 mm in size was 30% and 81.5%, respectively (p = 0.024). Sensitivity of CTA for posterior communicating artery (PComm) aneurysms was 56% and lower than other major anterior circulation locations (83% – 91%) (p = 0.045). Conclusion: The CTA diagnostic efficiency was lower than previously reported, with even lower sensitivity for aneurysms < 3 mm and for those arising from the PComm. Thus, CTA should remain a screening tool prior to DSA in all local patients suspected to have aneurysmal SAH.
Keywords: Digital subtraction angiography; DSA; Computed tomography angiography; CTA; Intracranial aneurysms; Ruptured aneurysms; Comparison; Accuracy; Diagnosis; SDG-3: Good health and well-being; SDG-17: Partnerships for the goals